2021
DOI: 10.3390/insects12111037
|View full text |Cite
|
Sign up to set email alerts
|

Hornets and Honey Bees: A Coevolutionary Arms Race between Ancient Adaptations and New Invasive Threats

Abstract: Hornets and honey bees have a long history of coevolution resulting in a plethora of captivating adaptations and counteradaptations between predator and prey. From simple physiological mechanisms to complex behavioral strategies, some Vespa hornets have specialized in hunting honey bees, while the latter have put in place effective defenses to counteract their attack. Both hornets and honey bees have evolved the ability to detect the odors and the pheromones emitted by the other to locate the prey or to spot f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 115 publications
(308 reference statements)
0
21
0
Order By: Relevance
“…After approximately a month, workers emerge and the colony develops throughout spring and summer reaching a peak of thousands of individuals in late summer/beginning of fall. Workers attend to the activities previously performed by the queen while she continues with her main role of oviposition; therefore, workers are busy providing food for the brood, cleaning and enlarging nest ( Cappa et al., 2021 ). Between September and December the colony population drops, meanwhile new queens and drones enclose and soon mate.…”
Section: Introductionmentioning
confidence: 99%
“…After approximately a month, workers emerge and the colony develops throughout spring and summer reaching a peak of thousands of individuals in late summer/beginning of fall. Workers attend to the activities previously performed by the queen while she continues with her main role of oviposition; therefore, workers are busy providing food for the brood, cleaning and enlarging nest ( Cappa et al., 2021 ). Between September and December the colony population drops, meanwhile new queens and drones enclose and soon mate.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, apiaries have to be often adapted, and it is suggested to form lines with a reduced distance between hives in order to reduce the distance from hive entrances to the harp, to achieve a higher protective effect. 28 Nevertheless, in this study, we observed that in apiaries placed in sites with a high abundance of V. velutina, with a compact line of hives (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) cm separation between them) and one harp between two consecutive hives, the reduction of hunting pressure was significant but still not enough to achieve a null predation. Therefore, in highly invaded areas, this control method should be deployed in tandem with additional measures, such as V. velutina's nest detection and destruction in the surroundings of the apiaries in order to reduce the number of hunters and their detrimental consequences on honey bee colony performance and survivorship.…”
Section: Management Of Apiaries In Invaded Areasmentioning
confidence: 62%
“…19 Western honey bees (Apis mellifera Linnaeus, 1758) perform defensive behaviors in response to hornet attacks. 20 Nevertheless, these are ineffective in reducing hunting pressure, allowing hornets to intensively predate honey bees at hive entrances. 21 This increases the expression of genes associated with oxidative stress, potentially harming bee health in colonies under attack.…”
Section: Introductionmentioning
confidence: 99%
“…Hornets are major predators of A. dorsata hives (Kastberger et al, 2013;Seeley et al, 1982), and Vespa tropica (the greater banded hornet) is a common predator in our study location (Balamurali et al, 2021). Moreover, hornets can act as strong evolutionary drivers in the evolution of specialised anti-predatory responses in honeybees (Cappa et al, 2021;Ken et al, 2005;Mattila et al, 2020;Mattila et al, 2021;Papachristoforou et al, 2007;Tan et al, 2013). Shimmering resembles the anti-hornet 'I-see-you' display found in the sympatric cavity-nesting A. cerana in which guard bees at the entrance shake their abdomens in a to-and-fro motion in the presence of hornets, which supposedly warns the predator that the bees have detected its presence (Tan et al, 2013).…”
Section: Discussionmentioning
confidence: 81%